Microfluidic size exclusion chromatography (μSEC) for extracellular vesicles and plasma protein separation - Leong, Sheng Yuan (2022)
Extracellular vesicles (EVs) are recognized as next generation diagnostic bio-markers due to their disease-specific biomolecular cargoes and importance in cell–cell communications. A major bottleneck in EV sample preparation is the inefficient and laborious isolation of nanoscale EVs (≈50–200 nm) from endogenous proteins in biological samples. Herein, a unique microfluidic platform is reported for EV-protein fractionation based on the principle of size exclusion chromatography (SEC). Using a novel rapid (≈20 min) replica molding technique, a fritless microfluidic SEC device (μSEC) is fabricated using thiol-ene polymer (UV glue NOA81, Young’s modulus ≈1 GPa) for high pressure (up to 6 bar) sample processing. Controlled on-chip nano-liter sample plug injection (600 nL) using a modified T-junction injector is first demonstrated with rapid flow switching response time (<1.5 s). Device performance is validated using fluorescent nanoparticles (50 nm), albumin, and breast cancer cells (MCF-7)-derived EVs. As a proof-of-concept for clinical applications, EVs are directly isolated from undiluted human platelet-poor plasma using μSEC and show distinct elution profiles between EVs and proteins based on nanoparticle particle analysis (NTA), Western blot and flow cytometry analysis. Overall, the optically transparent μSEC can be readily automated and integrated with EV detection assays for EVs manufacturing and clinical diagnostics.